2019
DOI: 10.1177/0899764019869537
|View full text |Cite
|
Sign up to set email alerts
|

Look to Others Before You Leap: A Systematic Literature Review of Social Information Effects on Donation Amounts

Abstract: People are often influenced by information about other people’s behavior, that is, social information. Social information is frequently used by practitioners hoping to increase charitable giving, while the precise mechanisms through which social information works are unknown. We conducted a systematic literature review of 35 studies reporting on the effects of social information on charitable giving. We show that several studies report no or even negative effects and that a theoretical understanding of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 63 publications
2
76
0
Order By: Relevance
“…Donors adjust their charitable behavior according to social information. When individuals are presented with information on the donation amount of previous donors their donation amount increases (for example Alpizar, Carlsson, & Johansson-Stenman, 2008a;Bekkers, 2012;Edwards & List, 2013;Martin & Randal, 2008;Shang, Croson & Reed, 2012;van Teunenbroek, 2016;van Teunenbroek et al, 2020). Only three studies (Croson & Shang, 2008;Kubo, Shoji, Tsuge, & Kuriyama;Meyer & Yang, 2015) that examined effects of social information (reviewed by van Teunenbroek et al, 2019) reported a negative effect on the individual donation amount.…”
Section: The Effects Of Social Information In Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Donors adjust their charitable behavior according to social information. When individuals are presented with information on the donation amount of previous donors their donation amount increases (for example Alpizar, Carlsson, & Johansson-Stenman, 2008a;Bekkers, 2012;Edwards & List, 2013;Martin & Randal, 2008;Shang, Croson & Reed, 2012;van Teunenbroek, 2016;van Teunenbroek et al, 2020). Only three studies (Croson & Shang, 2008;Kubo, Shoji, Tsuge, & Kuriyama;Meyer & Yang, 2015) that examined effects of social information (reviewed by van Teunenbroek et al, 2019) reported a negative effect on the individual donation amount.…”
Section: The Effects Of Social Information In Previous Studiesmentioning
confidence: 99%
“…The prevailing explanation why social information works is that information about the decision of others creates a social norm (Bøg, Harmgart, Huck, & Jeffers, 2012;Croson et al, 2009;Croson & Shang, 2008, 2013Edwards & List, 2013;Meyer & Yang, 2015;Murphy et al, 2015;van Teunenbroek et al, 2020;Sasaki, 2018;Smith et al, 2015). The average donation amount provides a cue about what is typically done by others.…”
Section: The Effects Of Social Information In Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Teunenbroek et al (2019) suggest diffusion of responsibility: the higher threshold may convey social information that suggests that others donate more, thus, rendering the own donation as less meaningful. This interpretation would also be broadly in line with a non-behavioral model of…”
mentioning
confidence: 99%